2018
DOI: 10.1016/j.jval.2018.09.2522
|View full text |Cite
|
Sign up to set email alerts
|

Pss22 - Economic Burden of Disease of Hidradenitis Suppurativa in Finland: Results From the Hi-Fi Study

Abstract: OBJECTIVES: Lichen planus is a dermatological disease characterized by itchy reddish-purple polygon-shaped skin lesions. The aim of our study was to calculate the annual health insurance treatment cost of lichen planus in Hungary. METHODS: The data were derived from the financial database of the Hungarian National Health Insurance Fund Administration (NHIFA), the only health care financing agency in Hungary. We analyzed the number of patients and the health insurance treatment cost for the year 2017. The follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 0 publications
0
4
0
2
Order By: Relevance
“…Patients with Inflammatory bowel disease (IBD) and HS, had higher mean cost of hospitalization comparing to their IBD‐only counterparts ($ 1,035 absolute difference, P = 0.013) [27, 28]. Obese HS patients and those also suffering from metabolic diseases also incur higher annual costs [28]. A recent study by van Straalen et al.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Patients with Inflammatory bowel disease (IBD) and HS, had higher mean cost of hospitalization comparing to their IBD‐only counterparts ($ 1,035 absolute difference, P = 0.013) [27, 28]. Obese HS patients and those also suffering from metabolic diseases also incur higher annual costs [28]. A recent study by van Straalen et al.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with Inflammatory bowel disease (IBD) and HS, had higher mean cost of hospitalization comparing to their IBD-only counterparts ($ 1,035 absolute difference, P = 0.013) [27,28]. Obese HS patients and those also suffering from metabolic diseases also incur higher annual costs [28]. A recent study by van Straalen et al showed that HS patients are more likely to be obese or overweight at disease onset compared to healthy, age-matched controls, which could potentially mean that increased weight predisposes to HS development, at least in a subgroup of patients [29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patienten mit chronisch‐entzündlichen Darmerkrankungen (CED) und HS hatten höhere durchschnittliche Krankenhauskosten im Vergleich zu Patienten, die nur an CED erkrankt waren (absolute Differenz 1.035 $, P = 0,013) [27, 28]. Adipöse HS‐Patienten und Patienten mit Stoffwechselerkrankungen verursachen ebenfalls höhere jährliche Kosten [28]. Eine vor kurzem veröffentlichte Studie von van Straalen et al.…”
Section: Diskussionunclassified
“…The economic burden of HS is high, with direct medical costs due to surgery being estimated at £2,027 per patient per year in the UK [10]. Medical costs are observed to be up to 2.4 times higher for more severe HS patients [11]. Indirect costs associated with frequent and long-term A c c e p t e d M a n u s c r i p t absenteeism and disability costs of HS patients further add to the socioeconomic burden of HS [12].…”
Section: Introductionmentioning
confidence: 99%